A novel three-dimensional molecularly imprinted polypyrrole electrochemical sensor based on MOF derived porous carbon and nitrogen doped graphene for ultrasensitive determination of dopamine. Issue 22 (17th October 2022) - Bu, Liyin; Jiang, Ding; Song, Qingyuan; Shan, Xueling; Wang, Wenchang; Chen, Zhidong
Abstract : The fabrication processes of Ppy–MIP/ZrO2 @C/NPG/GCE. Abstract : Herein, a novel molecular imprinting polypyrrole electrochemical sensor was fabricated based on a zirconia and carbon core–shell structure (ZrO2 @C) and a nitrogen-doped graphene (NPG) modified glassy carbon electrode (GCE) for ultrasensitive recognition of dopamine (DA). The NPG was prepared by a sacrificial-template-assisted pyrolysis method and ZrO2 @C was synthesized via annealing treatment of a zirconium-based metal–organic framework (UiO-66). A convenient electropolymerization method was used to prepare the pyrrole (Py) conductive molecularly imprinted polymer (MIP) in the presence of DA. The elution process of DA was performed by a simple overoxidation process under alkaline conditions. Differential pulse voltammetry (DPV) was used to assess the electrochemical performance of the sensors. The MIP-based electrochemical sensor with specific binding sites could be used for selective recognition of DA. Under the optimal conditions, the linear range of such a sensor was 5.0 × 10 −9 –1.0 × 10 −4 mol L −1 and the detection limit was 3.3 × 10 −10 mol L −1 (S/N = 3). This sensor exhibited suitable selectivity, stability, and reproducibility, which suggested that it could be a promising candidate for rapid diagnostic methods in dopamine investigations.